Upaya Peningkatan Pengetahuan dan Sikap dalam Pemanfaatan Limbah Cangkang Kerang menjadi Produk Tepung Kaya Kalsium: Efforts to Improve Knowledge and Attitudes in Utilizing Shellfish Waste into Calcium-Rich Flour Products - Achmad, Anisyah; Nurdiani, Rahmi; Danimayostu, Adeltrudis Adelsa; Harti, Leny Budhi; Dini, Martina; Irsani, Intaha; Asyiqin, Melfin Fakhrul; Maulana, Sulung Rival Isom; Putra, Juanda Riztama (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Pejagan Village in Bangkalan Regency, East Java, has a population of around 6,500 people with the majority working in the agriculture and fisheries sectors, supported by the Mutiara Laut Cooperative which provides economic services. The village community has local natural potential such as korkor clams and scallops. So far, clam meat has been sold to restaurants outside Madura to improve the family economy, but the shells often become waste due to a lack of processing knowledge. Shell waste is scattered on the side of residents' houses or the side of village roads and gives an unpleasant aroma to the surrounding community. This community service activity was carried out to educate residents about the benefits of shell waste in calcium-rich flour using counseling methods, leaflets, questions and answers, and evaluation using questionnaires. Respondents who are residents around the Mutiara Laut Cooperative are women, most of whom are wives of local fishermen, invited to be given increased knowledge and changes in attitudes toward the use of shell waste.